DEVELOPMENT OF FERROUS METALLURGY IN UZBEKISTAN IN THE CONTEXT OF MODERNIZATION OF THE NATIONAL ECONOMY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In article consider perspectives develop black metallurgies Uzbekistan in examples Uz metkombinat. Production produces black metallurgy in the Gase only for the second time raw material hisnot real perspective for growth and provide demand republic. For stable develops branch need to create own raw material base, to have location republic of Uzbekistan.